HTML & CSS essentials - McFedries, Paul (For Dummies, 2024)
The easy way to brush up on your HTML & CSS programming skills HTML & CSS Essentials For Dummies is your quick and handy reference to all the core concepts of HTML & CSS--the must-know markup and style languages that make the internet go. This no-nonsense book gets right to the point, eliminating review material, wordy explanations, and fluff. Understand all the fundamentals of HTML and CSS, quickly. Perfect for a brush-up on the basics or as an everyday desk reference on the job, this is the reliable little book you can always turn to for answers. Get simple explanations of the basic concepts of coding with HTML & CSS Review what you've already learned or pick up essential new skills Create attractive and functional front ends for websites of all kinds Keep this concise reference book handy for jogging your memory as you work This book is clear and direct, focusing on the key topics you need to know about defining a website's user interface. Great for supplementing classroom learning, reviewing for a certification, or staying knowledgeable on the job.
Keywords: HTML (Document markup language); Cascading style sheets; HTML (Langage de balisage); Feuilles de style en cascade; HTML